Analysis of Students' Problem-Solving Abilities in Solving HOTS Questions on Kinematics Topics - Ummul Khaeri; Usman Usman; Mutahharah Hasyim; Trisno Setiawan (Universitas Lambung Mangkurat, 2026)
Problem-solving skills based on Higher Order Thinking Skills (HOTS) are very important in learning physics, but many students still have difficulty meeting the indicators of high-level thinking. The gap between understanding the problem and the ability to design a solution strategy shows the need for a more in-depth analysis of the students' thinking process. This study aims to analyze students’ problem-solving abilities in answering physics questions based on HOTS using Polya’s four problem-solving steps: understanding the problem, devising a plan, carrying out the plan, and looking back. The study employed a quantitative descriptive approach involving 32 eleventh-grade students during the second semester of the 2024/2025 academic year. The research instrument consisted of five HOTS-based essay questions that had been tested for validity using the Gregory technique. The analysis results showed a validity coefficient of 1.00, indicating that the instrument is highly valid and appropriate for measurement. In addition, the instrument also meets the reliability criteria, so it is declared suitable for use in the collection of research data, and the data were analyzed according to the students’ performance in each problem-solving stage. The findings indicate that the “understanding the problem” stage was the most mastered aspect, with most students categorized as high and very high. In contrast, the “devising a plan” stage showed the lowest achievement, with the majority falling into the very low category. Overall, students’ problem-solving abilities varied considerably, particularly in planning strategies and executing solutions. These results suggest the need for instructional practices that better develop students’ strategic planning, systematic thinking, and higher-order reasoning skills.